The confiscation of private Ecuadorian media during Rafael Correa’s government and its consequences - Panchana-Macay, Allen (2023)
The case of the private media confiscated in Ecuador at the beginning of Rafael Correa’s presidency (2007 – 2017) led to complex economic, legal, and professional circumstances for the media companies and their journalists. This paper aims to share a broad and documented perspective on the origin and development of the issue at hand by combining three methods for its approach: the historical method, analysis of media policies and in-depth interviews. Implementing regulatory procedures to devise structures for adjustment and censorship towards private media promoted a media reshaping that resulted on the stockpiling of important nationwide media companies (TV, radio, and magazines) into the state-owned entities umbrella. These confiscations took place at a sensitive time for the banking system that owned several of these media, which had been affected by a severe economic, social, and political crisis. The legal actions filed by owners of the confiscated media have rendered it impossible to sell the companies. Furthermore, the precarious financial status turned them into undesirable targets for possible buyers. Out of the seventeen privates media companies owned by the government in 2008, only two are still active in 2023. The other fifteen companies went bankrupt or are currently undergoing liquidation. This measure, while advantageous for the political power, represented an economic and journalistic failure.